2022
DOI: 10.2147/rmhp.s338121
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Characteristics and Transmission Patterns of COVID-19 Cases Among Children and Adolescents Aged 0–18 Years in South Korea

Abstract: Background: In South Korea, the epidemiological characteristics of children and adolescents infected with severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) have not been reported to date. The purpose of this study was to identify major epidemiological characteristics and transmission patterns of coronavirus disease 2019 (COVID-19) in children and adolescents. Methods: This study was conducted through a system integrated in an epidemiological investigation by the Korea Disease Control and Prevention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…As the immune system undergoes changes in children and adolescents ( Bartlett et al, 1998 ), two age groups were considered: ≤ 12 years and 13–17 years. Moreover, the previous epidemiological studies have shown that individuals aged 13–17 years are far more likely to be infected with SARS-CoV-2 and experience symptomatic infection than ≤ 12 years ( Jang et al, 2022 , Ryan et al, 2022 ). Moreover, in the present study, these two age groups had a similar sex distribution and did not differ in frequencies of comorbidities.…”
Section: Methodsmentioning
confidence: 99%
“…As the immune system undergoes changes in children and adolescents ( Bartlett et al, 1998 ), two age groups were considered: ≤ 12 years and 13–17 years. Moreover, the previous epidemiological studies have shown that individuals aged 13–17 years are far more likely to be infected with SARS-CoV-2 and experience symptomatic infection than ≤ 12 years ( Jang et al, 2022 , Ryan et al, 2022 ). Moreover, in the present study, these two age groups had a similar sex distribution and did not differ in frequencies of comorbidities.…”
Section: Methodsmentioning
confidence: 99%
“…During the Omicron period, the estimated effectiveness of a primary cycle significantly decreased in time, resulting in an overall effectiveness equal to 35% (34-37) among children and 19% (16)(17)(18)(19)(20)(21) among adolescents. Third doses, available just for adolescents during the Omicron period, provided an overall VE of 38% (36-40).…”
Section: Incidence Of Sars-cov-2 Infections Per Vaccine Status and Va...mentioning
confidence: 99%
“…In the Omicron scenario, the overall effectiveness afforded by a primary cycle with BNT162b2 among children was 35% (34)(35)(36)(37) and it ranged from 72% (69-74) in the first week from vaccination to 23% (20)(21)(22)(23)(24)(25)(26) after more than 70 days from vaccination. The primary cycle with the same vaccine among adolescents provided an overall VE of 17% (15)(16)(17)(18)(19)(20) with an initial value of 81% (76-85), which decreases until 8% (5)(6)(7)(8)(9)(10)(11). The overall protection afforded by a primary cycle with mRNA-1273 among adolescents was 30% (26)(27)(28)(29)(30)(31)(32)(33), ranging from 88% (81-92) in the first week to 20% (15)(16)(17)(18)(19)(20)(21)(22)(23)(24) after more than 10 weeks.…”
Section: Incidence Of Sars-cov-2 Infections Per Vaccine Status and Va...mentioning
confidence: 99%
See 1 more Smart Citation
“…Even when infected, children usually develop milder disease (17) and emit fewer virus particles than adults (18). Outbreaks among schools report low secondary attack rates (4,19) with child-tochild transmission, which is significantly lower than adult-to-adult and adult-to-child transmission (19)(20)(21)(22). However, several studies have noted an important distinction between transmission among young children (age 6-12) and adolescents (23,24) with reports of larger and more frequent outbreaks among secondary schools (25).…”
Section: Studies In Europementioning
confidence: 99%